Policy instruments for managing road safety on EU-roads - Laurinavičius, Alfredas; Juknevičiūtė-Žilinskienė, Lina; Ratkevičiūtė, Kornelija; Lingytė, Ineta; Čygaitė, Laura; Grigonis, Vytautas; Ušpalytė-Vitkūnienė, Rasa; Antov, Dago; Metsvahi, Tiit; Toth-Szabo, Zsuzsanna; Várhelyi, András (Transport, 2012)
Directive 2008/96/EC on road infrastructure safety management requires the establishment and implementation of procedures relating to road safety impact assessments (RSIA), road safety audits (RSA), ranking of high accident concentration sections and network safety ranking (NSR) and road safety inspections (RSI). The aim of this article is to present the outputs of BALTRIS project. The goal of the international project BALTRIS is to elaborate the road and street infrastructure safety management procedures and teaching material consistently explaining the above mentioned infrastructure management procedures. Four Baltic Sea region countries (Sweden, Estonia, Latvia, and Lithuania), represented by universities and national road administrations participate in the elaboration of these procedures and teaching material. This article describes the scope of NSR, RSA and RSI procedures prepared in the frame of BALTRIS project, also article provides detailed implementation and execution of procedures for the EU Member States. NSR means a method for identifying, analysing and classifying parts of the existing road network according to their potential for safety development and accident cost savings. Ranking of high accident concentration sectionsmeans a method to identify, analyse and rank sections of the road network which have been in operation for 3÷5 years and upon which a large number of fatal/injury accidents in proportion to the traffic flow or compared to respective conditions have occurred. RSI is a strategic comparative analysis of the impact of the new road or a substantial modification to the existing network on the safety performance of the road network. RSA is a formal safety performance examination of the existing or future road or intersection by an independent audit team. First Published Online: 21 Dec 2012